2021
DOI: 10.1227/neu.0000000000001734
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Summation Predicts De Novo Contralateral Pain After Cordotomy in Patients With Refractory Cancer Pain

Abstract: BACKGROUND: Percutaneous cervical cordotomy (PCC), which selectively interrupts ascending nociceptive pathways in the spinal cord, can mitigate severe refractory cancer pain. It has an impressive success rate, with most patients emerging pain-free. Aside from the usual complications of neurosurgical procedures, the risks of PCC include development of contralateral pain, which is less understood. OBJECTIVE: To evaluate whether sensory and pain sensitivity, as measured by quantitative sensory testing (QST), are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Although assessing TS is a reliable way to evaluate altered pain processing, no studies in HNC patients were found to evaluate it. It has been proven to be a valid tool in other pathologies involving chronic pain as breast and endometrial cancer, hip arthroplasty, or fibromyalgia [ 32 – 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although assessing TS is a reliable way to evaluate altered pain processing, no studies in HNC patients were found to evaluate it. It has been proven to be a valid tool in other pathologies involving chronic pain as breast and endometrial cancer, hip arthroplasty, or fibromyalgia [ 32 – 34 ].…”
Section: Discussionmentioning
confidence: 99%